BMUS journal club on Twitter: An analysis of the first #BMUS_JC discussions. (August 2021) - Reeve, Ruth; Moore, Stephen; Kirkpatrick, Catherine
Introduction: Journal clubs have evolved over recent years within healthcare to encourage continuing professional development. More recently, there has been a move from face-to-face group meetings to virtual groups utilising social media platforms. This article aims to explore the discussions and narrative following the inaugural BMUS journal club, highlighting the key discussions and themes from the participants and to provide a narrative for the future of ultrasound continuing professional development. Methods: The August 2020 journal club chat was focussed on the article featured in Ultrasound : "Sonographers' level of autonomy in communication in Australian obstetric settings: Does it affect their professional identity?" by Thomas et al. Data consisting of Twitter correspondence were extracted and analysed from the advanced search function on Twitter using #BMUS_JC thread. An initial review ensured related content was included. A second review and semantic thematic analysis was then conducted on the 123 tweets. Results: In total, seven overall themes were identified between the three sub-threads within the journal club discussions. Those participating in the Twitter discussion recognised the limitations and barriers for communicating results to patients, acknowledging that training, support and regulatory involvement is required for sonographers to change practice locally and internationally. Conclusion: The group discussions on Twitter highlight the ongoing issues for sonographers' professional identity worldwide. Furthermore, our analysis echo other contemporary studies which indicate that Twitter journal clubs act as a fruitful and dynamic source of continuing professional development, particularly in an era where social distancing is encouraged. The outcomes of the first BMUS journal club support the wider evidence that online journal clubs can provide a successful platform for professional discussion and debate.